1997
DOI: 10.1590/s0074-02761997000200005
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis in Ecuador: Prevalence of Infection on the Ecuador-Colombia Border in the Province of Esmeraldas

Abstract: The prevalence of onchocerciasis infection was determined in communities on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…This is further confirmed by the negative results of a rapid epidemiologic assessment carried out in the Canton San Lorenzo in Ecuador, 10 just across the border from where the present study was carried out.…”
Section: Discussionsupporting
confidence: 81%
“…This is further confirmed by the negative results of a rapid epidemiologic assessment carried out in the Canton San Lorenzo in Ecuador, 10 just across the border from where the present study was carried out.…”
Section: Discussionsupporting
confidence: 81%
“…The present population on the Cayapas River consists primarily of two groups: Chachi Amerindians (also known as Cayapa) and Afro-Ecuadorians. In the area covered by this study, both groups had populations of about 1,600-1,700 in the early 1980s (Guderian et al, 1983). Chachi oral tradition states that they migrated into Esmeraldas Province from the highlands north of Quito a t about the time of Spanish conquest, first settling on the upper Santiago River and only later moving into the area they presently inhabit (Barrett, 1925).…”
Section: Methodsmentioning
confidence: 89%
“…In this same year the possibility of a second transmission focus in the rural area of Tumaco, on the border with Ecuador, was ruled out [15]. This was further confirmed by the negative results of a rapid epidemiologic assessment carried out in Ecuador in 19 communities along or adjacent to the Mataje River which forms the border between Colombia and Ecuador [16]. Thus, it was concluded that onchocerciasis in Colombia was confined to the single focus of Lopez de Micay, specifically to the village of Naicioná, on the Pacific Coastal Plain of the country, along the Micay River basin.…”
Section: Introductionmentioning
confidence: 90%